2013
DOI: 10.1063/1.4812581
|View full text |Cite
|
Sign up to set email alerts
|

Modeling mechanophore activation within a crosslinked glassy matrix

Abstract: II. METHODS The continuum activation model developed herein relies on two smaller scale simulation methods (molecular a)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 21 publications
0
46
0
Order By: Relevance
“…For all experiments the onset of mechanical activation occurs at a larger strain than the yield peakas is consistent with other literature on SP-linked PMMA (Table 1). 12,24 Like the yield strain, the onset of activation strain increases with increasing strain rate and is larger for compression than for tension. The trend for strain at the onset of activation is in fact more exaggerated than the trend for yield strain (quadratic vs log strain rate).…”
Section: Resultsmentioning
confidence: 99%
“…For all experiments the onset of mechanical activation occurs at a larger strain than the yield peakas is consistent with other literature on SP-linked PMMA (Table 1). 12,24 Like the yield strain, the onset of activation strain increases with increasing strain rate and is larger for compression than for tension. The trend for strain at the onset of activation is in fact more exaggerated than the trend for yield strain (quadratic vs log strain rate).…”
Section: Resultsmentioning
confidence: 99%
“…Silberstein et al found a non-equilibrium state resulting in local force fluctuations in glassy polymers. 5 The MD simulation results showed good agreement between the onset of strain softening (first kink) and the onset of mechanophore activation. Based on the damage analysis in the MD simulation, there are micro cracks when the local strain is 8%, associated with the observed initial kink point of the stress-strain curve.…”
Section: B Strain Based Damage Evaluation To Predict Failurementioning
confidence: 70%
“…[1][2][3][4] Mechanophores, which are covalently linked into polymers, is a result of the transmission of external forces at the macroscale to the debonding of covalent links at the molecular level. [4,5] Therefore, itprovides a novel means for designing smart materials with self-sensing capability. Cho et al [6,7] have developed a cyclobutane-based mechanophore comprised of carbon-carbon covalent bonds that transform into cinnamate groups and emit visible fluorescence under external loading.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the extensive efforts devoted to syntheses of MCR polymers, very few models have been developed to reveal intricate interplays between mechanical forces and chemical reactions in MCR polymers. Recently, elastic and viscoelastic models for MCR glassy polymers [23] and elastomers [24,25] have been reported. While these models are consistent with some experimental data, they fail to explain other important experimental phenomena.…”
Section: Introductionmentioning
confidence: 99%